Pilot Study of the Effects of Bright Ambient Therapy on Dementia Symptoms and Cognitive Function - Liu, Chuen-Ru; Liou, Yiing Mei; Jou, Jwo-Huei (Frontiers in Psychology, 2021)
Light therapy potentially improves dementia symptoms. In this study, we examined the effects of bright light therapy on neuropsychiatric behaviors and cognitive function. Thirty-five participants were assigned to either the experimental or comparison group. The experimental group was exposed to bright light at 2,500 lux, and the comparison group was exposed to 114–307 lux. The instruments used were the Neuropsychiatric Inventory and the Mini-Mental State Examination. The experimental group showed a significant improvement in Neuropsychiatric Inventory scores; these scores, which were calculated using generalized estimating equations with medication (benzodiazepines) as a covariate, were reduced by 65% (P < .001) and 78% (P = .001) by the 5th and 9th weeks, respectively. At the same time, Mini-Mental State Examination scores increased by 19% (P = .007) and 28% (P = .04), respectively. However, differences in outcomes between the 5th and 9th weeks were not significant. A four-week regimen of bright light therapy was the most effective, with higher adherence and acceptability.